2002
DOI: 10.1523/jneurosci.22-15-06415.2002
|View full text |Cite
|
Sign up to set email alerts
|

Postsynaptic Targeting of Alternative Postsynaptic Density-95 Isoforms by Distinct Mechanisms

Abstract: Members of the postsynaptic density-95 (PSD95)/synapse-associated protein-90 (SAP90) family of scaffolding proteins contain a common set of modular protein interaction motifs including PDZ (postsynaptic density-95/Discs large/zona occludens-1), Src homology 3, and guanylate kinase domains, which regulate signaling and plasticity at excitatory synapses. We report that N-terminal alternative splicing of PSD95 generates an isoform, PSD95beta that contains an additional "L27" motif, which is also present in SAP97.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
112
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(117 citation statements)
references
References 66 publications
5
112
0
Order By: Relevance
“…3c). This L27 domain-mediated polymerization model is consistent with experimental observations showing that L27 domain-containing scaffold proteins, such as SAP97 and mLin-2, often form large clusters 2,3,11,13,18,19 . During this L27 domainmediated scaffold protein assembly, other protein-binding domains (such as the PDZ and SH3 domains) would be free to recruit their specific target proteins (receptors, ion channels and their downstream partners).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…3c). This L27 domain-mediated polymerization model is consistent with experimental observations showing that L27 domain-containing scaffold proteins, such as SAP97 and mLin-2, often form large clusters 2,3,11,13,18,19 . During this L27 domainmediated scaffold protein assembly, other protein-binding domains (such as the PDZ and SH3 domains) would be free to recruit their specific target proteins (receptors, ion channels and their downstream partners).…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with earlier reports, mixing experiments using 15 N-labeled recombinant proteins showed that the L27S of SAP97 and L27N of mLin-2 formed a stable heteromeric complex and that the L27 domain of mLin-7 and L27C of mLin-2 formed another heteromeric complex 3,[13][14][15] (data not shown). We chose the L27S-L27N pair for further structural analysis owing to the better spectral quality of this complex ( Supplementary Fig.…”
supporting
confidence: 91%
See 3 more Smart Citations